Pengaruh Keseimbangan Kehidupan Kerja, Lingkungan Kerja, dan Kompensasi Terhadap Kinerja Polisi Satlantas Polres Kerinci - Suyatno Suyatno; Helmi Ali (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study aims to see (1) The effect of work-life balance on the performance of the Kerinci Police Satlantas Members, (2) The influence of the work environment on the performance of the Kerinci Police Traffic Unit members, (3) The effect of compensation on the performance of the Kerinci Police Traffic Unit members, (4) The effect of balance work life, work environment, and compensation for the performance of the members of the Satlantas Polres Kerinci. The population in this study were all members of the Jambi Police Mobile Brigade as many as 44 people. Sampel, 44 people were selected and the sample was selected by simple random sampling. The technique of determining the number of samples using total sampling. The data analysis technique used multiple regression by fulfilling the requirements of the classical assumption test of normality, and multicollinearity, heteroscedasticity. The results of this study indicate that (1) Work-life balance has a significant effect on the performance of the members of the Kerinci Police Traffic Unit, (2) the work environment has a significant effect on the performance of the members of the Kerinci Police Traffic Unit, (3) Compensation has a significant effect on the performance of the members of the Kerinci Police Traffic Unit, (4) Work-life balance, work environment, and compensation have a significant effect on the performance of the members of the Kerinci Satlantas Police